Determination of the Effects of Exposure to Emissions from Chemical Industry on Health, Environment and Regulation - Priscaningtyan; Widya Ernayati; Robby Zidny (Postgraduate, University of Mataram, 2026)
Rapid industrial growth in various regions of Indonesia has contributed significantly to the national economy. Pollution of air, water, and soil has become a critical concern when industrial activities are not managed in accordance with sustainability principles. This study aims to analyze the impact of emission exposure and operational activities of the chemical industry on public health, environmental conditions, and compliance with environmental regulations. A mixed-method approach was applied, combining quantitative and qualitative analyses. Quantitative data were obtained through air quality measurements and analyzed using linear regression and correlation techniques, while qualitative data explored regulatory compliance in greater depth. The findings reveal a positive correlation between increased emission exposure and higher incidences of respiratory disorders within the community. Environmental degradation was also evident, particularly in declining air quality and damage to surrounding vegetation. Although industrial practices generally comply with local environmental regulations, cases of Acute Respiratory Infections continue to rise. This indicates that regulatory compliance alone is insufficient to mitigate health risks. Therefore, stricter emission monitoring, improved transparency in environmental reporting, and enhanced community involvement are essential to support more sustainable and responsive industrial policies.